Techno-economic resilient planning strategy in microgrid islanded system with multiple renewable energy and energy storage system in Malaysia - Johari, Atikah (2022)
The purpose of this study is to enhance the conventional power distribution system’s resiliency via critical loads survival metric. A two-stage framework is proposed for this project, where each stage uses a different tool. In stage 1, the viability of using Hybrid Optimization of Multiple Energy Resources (HOMER) Grid software is explored to model a resilience and economic hybrid microgrid (MG) in Malaysia environment and subsequently the optimal distributed generation (DG) sizing is determined. The modeled MG that consists of Renewable Energy System (RES) and Energy Storage System (ESS) contributes to lowering the total net preset cost (NPC), levelized cost of energy (COE), as well as the carbon emissions. In stage 2, power flow study is performed by using Power World software. Optimal DG placement and switching strategy are applied together with the optimal DG size, to see the effectiveness compared to a benchmark system. IEEE 33-bus test system model is used to validate the proposed strategy. The resilience improvement of the proposed strategies was assessed under five worst-case scenarios and validated through nine case study. Finally, the resiliency of the power network is quantified by using a proposed resilient index (RI) formula. Numerical simulations and technical data demonstrate the effectiveness of the proposed resiliency planning strategies in a radial distribution system.